Examining the relationship between text-message dependency and psychological or behavioural symptoms from the perspective of self-perception theory / Melissa Shahrom ... [et al.] - Shahrom, Melissa; Ghazali, Norfazlina; Azmi, Farah Syazreena; Alwi, Anisah; Abdul Majid, Afiza (Universiti Teknologi MARA Cawangan Selangor, 2017)
The widespread use of smartphones and online text messages for communication has influenced and changed the everyday lives of its users. Undoubtedly, smartphones can enhance and advance our working life and personal life to suit modern lifestyles. However, some of the smartphone users show overdependence on the smartphone's applications especially on mobile communications to share and receive immediate information either for their work or personal related matters. 'Text-message dependency' is a term used to refer to these users who use and rely so much on text messaging applications. This obsessive use of mobile communications can lead to numerous psychological and behavioural symptoms such as problematic addictions, obsessions, health risks and also produce negative social outcomes. The research concentrates to study the factors that contribute to text-message dependency and psychological or behavioural symptoms from the perspective of self-perception theory. The research is significant and important for the society and national development in several aspects; 1) educate the society about the risks of smartphone addiction, 2) provide guidelines and insight to the ministry of health and multimedia development, and 3) give awareness to the application developers on the future demand of smartphone applications that relates to behaviour control.